2016
DOI: 10.1111/inm.12260
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with psychotic relapse in patients with schizophrenia in a Pakistani cohort

Abstract: Despite a large body of research evaluating factors associated with the relapse of psychosis in schizophrenia, no studies in Pakistan have been undertaken to date to identify any such factors, including specific cultural factors pertinent to Pakistan. Semistructured interviews and psychometric measures were undertaken with 60 patients diagnosed with schizophrenia (49 male and 11 female) and their caregivers at four psychiatric hospitals in the Peshawar region in Pakistan. Factors significantly associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 27 publications
3
36
0
2
Order By: Relevance
“…This instrument was adapted and validated for the Brazilian context in 2013 and contains 20 items, divided into two domains -CC (10 items -2, 4,6,8,10,12,14,16,18,20) and EOI (10 items -1, 3,5,7,9,11,13,15,17,19). The items in the two domains reflect different situations that the family members use to cope with their daily problems.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This instrument was adapted and validated for the Brazilian context in 2013 and contains 20 items, divided into two domains -CC (10 items -2, 4,6,8,10,12,14,16,18,20) and EOI (10 items -1, 3,5,7,9,11,13,15,17,19). The items in the two domains reflect different situations that the family members use to cope with their daily problems.…”
Section: Methodsmentioning
confidence: 99%
“…The family may be classified as having high EE if the family member that spends most of the time with the patient presents one or more of these components (2)(3) . Studies show that EE is a strong predictor of psychiatric relapses in schizophrenic patients, in different social and cultural contexts (4)(5) . A meta-analysis identified 27 articles reporting EE and psychiatric relapses in schizophrenia patients.…”
Section: Introductionmentioning
confidence: 99%
“…This is a concern as there are medicines and other strategies available to help address mental health disorders. However, inaccessibility to mental healthcare, as well as beliefs that psychiatric illness may be due to evil spirits and the neglect of ritual obligations, can result in patients approaching local religious healers, faith healers, hakims, or practitioners of homeopathic medicine, and potentially ultimately finding only limited relief (63,64). Pakistani women face an even greater risk as they can be targets of domestic violence and there are continuing concerns with gender-inequality including management of diseases such as mental health disorders.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there have been relatively few studies reporting on mental health conditions in Pakistan. Those that have been published include studies on common psychiatric disorders in outpatient care, general and major depressive disorders, factors associated with psychotic relapses and nonadherence of anti-psychotic medicines, gender differences in response to antipsychotics, cognitive disorders, and prescribing preferences of mental health professionals (7,13,64,(66)(67)(68)(69)(70)(71). However, we are not aware of any study that has comprehensively assessed utilization and expenditure patterns of antipsychotic medicines across Pakistan as a first step to improving treatment options if concerns.…”
Section: Introductionmentioning
confidence: 99%
“…EE is a relevant measure because several studies showed that people with mental disorders from families with high EE have a worse prognosis of the disease and more episodes of psychiatric acute than those from families with low EE (AHMAD et al, 2017;ZANETTI et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%